Optimizing in vitro Generation of Interleukin-10 Secreting B Regulatory Cells - K. S. Gupte; A. V. Vanikar; C. N. Patel; U. G. Thakkar (Recent Research Advances in Biology Vol. 10, 2021)
A major subset of IL-10 secreting B-cells, commonly characterized as CD19+/38hi/24hi, encompass B-regulatory cells (B-regs). We report effects of changes in stimulating molecule concentration on population of Interleukin-10 secreting B-regs of human origin. B-regs may be obtained from in-vitro co-culture of adipose tissue derived mesenchymal stromal cells (AD-MSC) and peripheral blood mononuclear cells (PBMC) for potential cell therapy. Lipopolysaccharide–E.coli-K12 strain (LPS-EK) was added in varying concentrations in the co-culture of AD-MSC and peripheral blood mononuclear cells (PBMC). At each time point, IL-10 concentration of cell supernatant was estimated by quantitative ELISA. Morphology, sterility, total count, viability and immune-phenotype of cells were determined. We analyzed the data to determine the time interval at which maximum B-reg population and optimum secretion of IL-10 was obtained. The present study provides precious information about the in vitro dynamics of IL-10 secretion by human B-regs generated from AD-MSC and PBMC. The present study focuses on in vitro generation of B-regs from adipose tissue derived mesenchymal stromal cells (AD-MSC) and peripheral blood mononuclear cells (PBMC), as well as on partial characterization of B-regs in terms of amount of IL-10 secreted, time taken and amount of stimulating molecule (i.e. LPS-EK) required for optimum IL-10 secretion. It has been reported that B-regs secrete cytokine in trace quantities. The medium which is added for feeding the cells further dilutes the secreted cytokines by many folds. In our study, the samples were appropriately concentrated, so that the cytokines could be detected by quantitative Enzyme Linked Immunosorbent Assay (ELISA).